PENGEMBANGAN SISTEM INFORMASI E – PETANI DAN IMPLEMENTASI SHORT MESSAGE SERVICE (SMS) GATEWAY HASIL ARGIBISNIS TANAMAN PERKEBUNAN KARET DAN SAWIT - Vincentius Abdi Gunawan; Marhayu Marhayu; Licantik Licantik; Nova Noor Kamala Sari (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2018)
The internet technology has been progressed very rapidly along by the time. It has resulted onefacility that is used in many aspects of living sector, known as website. Now, in the globalization era,website is used widely in many sectors of life such as education, social, health and business.This journal aims to create an information website of Electronic Farmer Agricultural OfficePulang Pisau Regency which uses notepad + +, PHP script and MySQL database that can be used onthe Windows operating system.The method that is used in collecting data such as interview by doing question and answerdirectly to the section that is connected to the object of the study. Direct observation is used to conveythe information. That is progressing in Electronic Farmer Agricultural Office Pulang Pisau Regencywith implementation SMS Gateway as a means of disseminating information to farmers andsurrounding communities. The literature review in collecting data by learning literature books aboutplan and design of one system. System design and data base planning are used by data flow diagram tocreate system model and entity relational diagram that describe the model of data relation.It is hoped the presence of this website can help the Agricultural Office Pulang Pisau Regencyin publish information Agricultural Office and information about farmers widely through the internetor by using SMS so that help people get information about Agricultural Office Pulang Pisau Regencyand information on prices of agricultural products.